2022
DOI: 10.1007/s00423-022-02480-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of postoperative day 1 parathyroid hormone levels for early and late hypocalcaemia after thyroidectomy

Abstract: Purpose Early parathyroid hormone (PTH) levels after total thyroidectomy can predict patients at low risk of hypocalcaemia who can be discharged early without calcium supplementation. For centres without facility to perform early PTH levels, PTH levels sent on the first postoperative day (POD1) may be an alternative. However, there is less data regarding optimal cut-off PTH levels for POD1 discharge. Methods Retrospective review of prospective database of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…A total of 1743 articles were screened (Figure 1) and 237 full‐text articles were assessed for eligibility. After careful selection of the articles, 66 studies were eligible for the final synthesis and were included in this review 10,14,23,24,27‐88 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 1743 articles were screened (Figure 1) and 237 full‐text articles were assessed for eligibility. After careful selection of the articles, 66 studies were eligible for the final synthesis and were included in this review 10,14,23,24,27‐88 …”
Section: Resultsmentioning
confidence: 99%
“…Screening identified 1619 abstracts of which 521 proved duplicates, leaving 1098 abstracts for review, of which 118 proved potentially eligible. Of these, 17 articles including 18 studies proved eligible ( 95‐111 ) (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…In Part I, eligible studies identified 170 complications and symptoms derived from 93 studies in 18,973 patients with chronic hypoparathyroidism. Of these, nine complications and symptoms were reported in three or more studies and occurred more often in patients with hypoparathyroidism than in individuals (96,98,103,109) 12-24 hours postoperative 12 (67) (95,97,(99)(100)(101)(102)104,105,107,108,110,111) Threshold Absolute value, pg/mL (pmol/L) ≤10 (1.05) 12 (66) (95,96,98,(100)(101)(102)104,107,(109)(110)(111) 10-15 (1.05-1.58) 4 ( 22) (99,103,105,108) Change in value >50% 1 (6) (97) <50% 0 Combination Absolute <9.3 pg/mL (0.98 pmol/L) and change of >86% 1 (6) (106) Timing of determination of chronic hypoparathyroidism after surgery 3 months (95,99,102,(104)(105)(106)(107)109) Timing of determination of chronic hypoparathyroidism 6 months 6 (67) (95,99,…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations